(3GdSffs - (3CHh HcQ CMeO Hf GdMSjf Hf Ydj GdNQGSGfj GdTGaYj, GdHjgbj,J (B458 (3g` s
(3ChdgG (B:s
(3CNHQfG GdTjN CHh HcQ CHh GdaJM CHh GdbGSe efUhQ Hf YHO GdefYe bGd CNHQfG GdEeGe CHh HcQ GdHjgbi bGd (B: (3GdMeO ddg HeG gh Cgdg s
(3BNQgG (B:s
(3HGdeMGaXI Ydi gGJjf GdUdGJjf HJYLjdgeG ai Chd hbJjgeG hHGddg GdJhajb BNQ GdLRA GdYTQjf s
(3HChdgG hBNQgG QhGjGJ hSeGYGJ dHYV GdYdeGAs
(3cJHJ GdYfGhjf HGdMeQIs
(3HgG eTgG HYV GdJYdjbGJ hGdJUMjMGJs
(3bQf GdfSN (B:s
(3GdbQf GdJGSYs
(3GdJhKjbGJ GdeQLYjI (B:s
Keywords: (3GdMOjK h GdeUWdMs